A multicentric knowledge-attitude-practice survey in the community about antimicrobial use and resistance in India. (19th November 2020) - Chatterjee, Suparna; Hazra, Avijit; Chakraverty, Raja; Shafiq, Nusrat; Pathak, Ashish; Trivedi, Niyati; Sadasivam, Balakrishnan; Kakkar, Ashish Kumar; Jhaj, Ratinder; Kaul, Rajni; Kshirsagar, Nilima
Abstract: Background: To address the reasons for inappropriate use of antimicrobials, it is important to understand the knowledge, attitude and practices (KAP) of all pertinent stakeholders. This multicentric survey is aimed at understanding the KAP quotients of the community regarding antimicrobial use and antimicrobial resistance (AMR), as such information is lacking in India. Methods: A cross-sectional survey was conducted by face-to-face interviews across five centers in India using a validated, field-tested questionnaire incorporating KAP domain questions. Scores were appropriately assigned to the questions. Results: The mean (SD) age of the respondents was 35.2 (12.61) y and 62% had a graduate or higher level of education. The median (IQR) KAP scores were 10 (8–12), 5 (3–5) and 2 (2–3) out of a maximum of 18, 5 and 6, respectively. Higher educational and socioeconomic levels were associated with better attitude scores, but knowledge levels were comparable. Correlations between KAP scores were poor. Conclusions: This study reveals that laypeople have appropriate knowledge and attitude regarding antibiotic use and AMR to some degree but there are important lacunae and practices are often wanting. These issues need to be addressed in sustained public awareness and motivation campaigns to improve the rational use of antibiotics in India.